Air temperature trends in Maribor as a consequence of the development of the urban heat islands - Žiberna, Igor (Journal for Geography, 2006)
Human influences, above all spreading of constructed areas, heating, air pollution, have contributed to the formation of a specific urban ecosystem. To its important characteristics belongs the appearance of a distinctive urban climate, which has been manifested through the construction of the urban heating and in the case of Maribor, as a consequence of human influences, above all spreading of constructed areas. Trends of the principal temperature indicators and of some other realized climate parameters are calculated. Influences of the urban heat island on selected bioclimatic indicators are represented as well.
Keywords: physical geography; city climate; Maribor